Applying strategies to the tennis challenge system - Pollard, G.; Pollard, G.; Barnett, T.; Zeleznikow, J. (Medicine and Science in Tennis, 2010)
This article gives an insight and provides strategies as to which points to challenge on to maximize a player`s chances of winning. This research could be used by players and coaches to possibly improve player performance.